Fodor's essential Greece 2023 - Amvrazi, Alexia; Brewer, Stephen; Clark, Gareth; Gauldie, Robin; McCaffrey, Liam; Vrettos, Adrian; Wallaya, Nora (Travel writer) (Fodor's Travel, a division of MH Sub I, LLC, dba Internet Brands, 2023)
"Ready to go away? The experts at Fodor's are here to help. We're bringing you the very best of Greece, including the Acropolis, Santorini, Meteora's monasteries, and more. Our local experts vet every recommendation to ensure that you have all the essential information to plan a perfect trip and make the most of your time"--Page 4 of cover.